2011
DOI: 10.5402/2011/385459
|View full text |Cite
|
Sign up to set email alerts
|

Positive Solutions for Boundary Value Problem of Nonlinear Fractional -Difference Equation

Abstract: We investigate the existence of multiple positive solutions to the nonlinear q-fractional boundary value problem c D a q u t a t f u t 0, 00, by using a fixed point theorem in a cone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 6 publications
0
50
0
Order By: Relevance
“…Ma and Yang [26] considered the existence of solutions for multi-point boundary value problems of nonlinear fractional q-difference equations by means of the Banach contraction principle and Krasnoselskii's fixed point theorem. El-Shahed and Al-Askar [20] studied the existence of multiple positive solutions to the nonlinear q-fractional boundary value problems by using GuoKrasnoselskii's fixed point theorem in a cone. Zhao et al [30] showed some existence results of positive solutions to nonlocal q-integral boundary value problem of nonlinear fractional q-derivatives equation using the generalized Banach contraction principle, the monotone iterative method, and Krasnoselskii's fixed point theorem.…”
Section: Introductionmentioning
confidence: 99%
“…Ma and Yang [26] considered the existence of solutions for multi-point boundary value problems of nonlinear fractional q-difference equations by means of the Banach contraction principle and Krasnoselskii's fixed point theorem. El-Shahed and Al-Askar [20] studied the existence of multiple positive solutions to the nonlinear q-fractional boundary value problems by using GuoKrasnoselskii's fixed point theorem in a cone. Zhao et al [30] showed some existence results of positive solutions to nonlocal q-integral boundary value problem of nonlinear fractional q-derivatives equation using the generalized Banach contraction principle, the monotone iterative method, and Krasnoselskii's fixed point theorem.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are few works consider the existence of positive solutions for nonlinear q-fractional boundary value problem (see [8,13,28,29]). As is well-known, the aim of finding positive solutions to boundary value problems is of main importance in various fields of applied mathematics (see the book [30] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…There have been some papers dealing with the existence and multiplicity of solutions or positive solutions for boundary value problems involving nonlinear fractional q-difference equations, such as the Krasnosel'skii fixed-point theorem, the Leggett-Williams fixed-point theorem, and the Schauder fixed-point theorem, For examples, see [8,9] and the references therein.…”
Section: Introductionmentioning
confidence: 99%